MoSexOy‐Coated 1D TiO2 Nanotube Layers: Efficient Interface for Light‐Driven Applications. Issue 3 (1st December 2017) - Ng, Siowwoon; Krbal, Milos; Zazpe, Raul; Prikryl, Jan; Charvot, Jaroslav; Dvořák, Filip; Strizik, Lukas; Slang, Stanislav; Sopha, Hanna; Kosto, Yuliia; Matolin, Vladimir; Yam, Fong Kwong; et al.
Abstract: Ultrathin molybdenum oxyselenide (MoSe x O y ) coatings are made first ever by atomic layer deposition (ALD) within anodic 1D TiO2 nanotube layers for photoelectrochemical and photocatalytic applications. The coating thickness is controlled through varying ALD cycles from 5 to 50 cycles (corresponding to ≈1–10 nm). In the ultraviolet region, the coatings have enhanced up to four times the incident photon‐to‐current conversion efficiency (IPCE), and the highest IPCE is recorded at 32% at (at λ = 365 nm). The coatings notably extend the photoresponse to the visible spectral region and remarkable improvement of photocurrent densities up to ≈40 times is registered at λ = 470 nm. As a result, the MoSe x O y ‐coated‐TiO2 nanotube layers have shown to be an effective photocatalyst for methylene blue degradation, and the optimal performance is credited to a coating thickness between 2 and 5 nm (feasible only by ALD). The enhancement in photoactivities of the presented heterojunction is mainly associated with the passivation effect of MoSe x O y on the TiO2 nanotube walls and the suitability of bandgap position between MoSe x O y and TiO2 interface for an efficient charge transfer. In addition, MoSe x O y possesses a narrow bandgap, which favors the photoactivity in the visible spectral region. Abstract : Atomic layer deposition–synthesized oxyselenide coatings on 1D TiO2 nanotubes layers act as efficient co‐photocatalyst. Increased light absorption, reduced optical bandgap, and formation of core‐shell‐like heterojunction due to ultrathin and uniform coatings within TiO2 nanotubes are accounted for enhanced photoelectrochemical activity of the resulting heterojunction and strongly enhanced photocatalytic activity in visible spectral region.